Transforming Inventory Management for Global Manufacturing Efficiency: Mengubah Manajemen Persediaan untuk Efisiensi Manufaktur Global - Winda Kharisma; Fityan Izza Noor Abidin (Academia Open, 2024)
This qualitative study explores the application of raw material inventory accounting information systems and internal control measures at PT. Perdana Sukses Makmur, a manufacturing company in Indonesia. Through interviews, observation, and documentation analysis, the research identifies that while the company's inventory system is well-implemented, certain internal control measures, such as the combination of functions and responsibilities, require improvement. These findings contribute to understanding inventory management practices in manufacturing firms, suggesting areas for enhancing internal control to improve production efficiency and organizational performance. Highlight: Efficient Inventory System: PT. Perdana Sukses Makmur demonstrates effective inventory management practices. Internal Control Challenges: Addressing function combination enhances organizational oversight. Production Efficiency Implications: Refining internal controls enhances manufacturing performance. Keywoard: Inventory Management, Internal Control, Manufacturing Company, Qualitative Study, Indonesia